2021
DOI: 10.3390/cryst11121507
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Ion Composition of Oligomineral Water and Calcium Oxalate Crystal Formation

Abstract: The ion content of drinking water might be associated with urinary stone formation, representing a keystone of conservative nephrolithiasis management. However, the effects of specific ions on calcium oxalate crystal formation and their mechanism of action are still highly controversial. We report an investigation of the effects of oligomineral waters with similar total salt amount but different ion composition on calcium oxalate (CaOx) precipitation in vitro, combining gravimetric and microscopic assays. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Furthermore, while research on cystinuria has primarily focused on clinical and genetic aspects to date, considering patient groups without SLC3A1/SLC7A9 mutations, it appears that additional studies are necessary, including research on the physicochemical factors related to cystine aggregation, similar to the results observed in calcium stone studies, and investigations into other urinary tract symptoms that may arise due to cystine crystal formation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while research on cystinuria has primarily focused on clinical and genetic aspects to date, considering patient groups without SLC3A1/SLC7A9 mutations, it appears that additional studies are necessary, including research on the physicochemical factors related to cystine aggregation, similar to the results observed in calcium stone studies, and investigations into other urinary tract symptoms that may arise due to cystine crystal formation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the detailed mechanism of the onset of OAB due to hypercalciuria is unclear, a recent report indicated that when hypercalciuria and hyperoxaluria co-exist, fine prenucleation nanoclusters of about 1 nm are formed at first, and the crystals gradually grow, depending on the conditions [ 19 ]. In addition, Rossi et al suggested that the ions/molecules contained in drinking water play an important role in the formation and growth of calcium crystals [ 20 ]. In other words, oligomineral water rich in magnesium (Mg) and sulfate reinforces the structure of water.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated its increase of interfacial energy and induction of the formation of large numbers of small crystals. As a result, over time, some crystals, especially calcium crystals, are oriented towards growing, leading to the formation of large crystals and agglomerates of particles [ 20 ]. Furthermore, chronic bladder irritation caused by these crystal components could cause urinary storage symptoms [ 1 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many dietary components affect calcium absorption, but some mineral waters rich in calcium have absorption efficiency very close to dairy products [ 59 ]. In addition, for children, water with low mineral content is recommended (except in certain specific cases, especially low calcium intakes), but several studies are underway to assess impacts of ion content of drinking water and calcium oxalate crystal formation [ 60 ].…”
Section: Place Of Hydration In Nephrolithiasis Treatmentmentioning
confidence: 99%